Exploration of the Benefits of Kusam as a Complementary Effort in Reducing the Intensity of Menstrual Pain in Adolescent Girls - Heni Rizka Aziza; Dwi Riyan Ariestantia (Newinera Publisher, 2025)
Many adolescent girls suffer from menstrual pain (dysmenorrhea), which can interfere with daily functioning, academic performance, and overall quality of life. While pharmacological treatments are commonly used, complementary therapies using natural ingredients such as turmeric and tamarind (known locally as kusam) have gained attention due to their safety and fewer side effects . The aim of this study was to assess how dullness can function as a supportive therapy to reduce the level of menstrual pain experienced by female adolescents at SMA Negeri 1 Batu Engau. A quantitative method was applied in this study, with a quasi-experimental design and pretest–posttest with a control group. Fifty eligible participants were divided into two groups: the intervention group received kusam (a turmeric and tamarind herbal drink) for three consecutive days at the beginning of menstruation, while the control group received no intervention. Pain intensity was measured using a Visual Analogue Scale (VAS), and the Wilcoxon test and the Mann–Whitney U test were applied to analyze the data. This study revealed a significant reduction in menstrual pain levels among the intervention group compared to the control group. The Wilcoxon test showed that the intervention group experienced significant improvement after consuming kusam (p < 0.05). Similarly, the Mann–Whitney U test showed a significant difference between the groups at post-test, with the intervention group achieving a higher mean score. Turmeric has been shown to be effective as a complementary treatment for reducing menstrual pain. intensity in adolescent girls.